STUDENTS’ PERCEPTION ON TEACHER’S LEARNING PROCESS WITH NON CIVIC EDUCATION BACKGROUND AT SMA BINA MULYA KEDATON - junia vamela; Adelina Hasyim; Yunisca Nurmalisa (FKIP Unila, 2012)
This research was objectives to explain how the students’ perception on teacher’s learning process with non civic education background at SMA Bina Mulya Kedaton Bandar Lampung 2011/2012. In this research, the researcher used descriptive method. The sample in this research was taken as 20% of the number of students was 35 students of SMA Bina Mulya Kedaton Bandar Lampung 2011/2012. The data collecting technique in this research was questionnaire, technical documentation, literature study and interview. Based on the calculation of data processing and data analysis, the result showed that the students’ perception on teacher’s learning process in pre-activity was 26 students (74,3%) included to good category, students’ perception on teacher’s learning process in while-activity was 19 students’ (54,3%) included to average category, 7 students (20%) included to bad category. Students’ perception on teacher’s learning process in post-activity 17 students (48,6%) inculed to good category. Keywords: students, learning process, non civic education background of the teacher.